Phytoplankton and trophic gradients : proceedings of the 10th workshop of the International Association of Phytoplankton Taxonomy & Ecology (IAP), held in Granada, Spain, 21-29 June 1996 - Alvarez-Cobelas, M. (Developments in hydrobiology, 1998)
These proceedings deal with the relationship between species composition of freshwater phytoplankton and the trophic gradient. Particular regard is paid to the composite question, what lives where and why? Overview papers report the state of the art and suggest that the trophic spectrum appears to be a probabilistic outcome of several dimensions of variability that impinge upon phytoplankton species selection. Studies on community structure span all latitudes from those of Antarctica to equatorial Brazil, and also include reports on light and nutrient gradients, pH and fish-stock effects on species composition. Seasonal and longterm phytoplankton dynamics in lakes of varying trophic status are also considered. Finally, studies on the taxonomy and autoecology of some groups (e.g. Volvocales, Chrysophytes and Euglenophytes) living at the extremes of the trophic spectrum contribute to our knowledge of this usually neglected phytoplankton. This is the first time that a book covers such a topic, and it will prove an excellent source of information to anyone working on phytoplankton ecology and ecological indicators. Limnologists in general, algologists and the technical staff at water authorities will all benefit by reading this book.